WORKSHOP PENERAPAN ASIS (APLIKASI SISTEM INFORMASI MANAJEMEN SEKOLAH) DI SD ISLAM CIHIDEUNGBALONG: WORKSHOP ON THE IMPLEMENTATION OF ASIS (SCHOOL MANAGEMENT INFORMATION SYSTEM APPLICATION) AT SD ISLAM CIHIDEUNGBALONG - Warnilah, Ai Ilah; Sutisna, Herlan; Pertiwi, Melisa Winda; Ratningsih; Ramdhani, Helmi; Arifah , Fahren Magfira; Nuraeni, Feni Siti (PADIMAS, 2024)
SD Islam Cihideungbalong is one of the educational institutions that has an important role in shaping future generations who are moral and knowledgeable. The problem is that SD Islam Cihideungbalong faces various challenges in managing school administration which is still done manually which results in data inaccuracy, low work efficiency, and difficulty in making data-based decisions. The solution offered for partners is the development of a school management system application with the aim of increasing the efficiency and accuracy of managing data on students, teachers, classes, subjects and alumni to facilitate access and management of information for stakeholders, improve the quality of education services through better data management. The expected benefits of this application are time and cost efficiency, increased data accuracy, easy access to information and facilitate accurate and real-time data-based decision making. With the implementation of this application, it is expected that school management will become more efficient and effective.